Operational Model of Cascading Values and Professional Ethics in Organization: A Context for Spiritual Development of Employees (Global Journal of Management and Business Research, 2012)
Compilation of vision, mission and strategies of organization causes systematic and directed movement of organization, but this movement without addressing business values and professional ethics will be spiritless and face serious challenges. To have successful, dynamic, spirited and sustainable business ,it is needed that moral values constitute its basic foundations. Successful business requires at least two major factors: i.e. competitive strategy and excellent performance in professional ethics. Act upon professional ethics is the major foundation of developed employees and managers in organization. Doing tasks, activities and achieving indicators and goals in moral atmosphere causes relation improvement, confidence making, healthy competition, development of capabilities and happiness in organization. Moral and spirituality are considered as requirements of today business world. So , with regard to importance of professional ethics in business, in this paper the concepts of moral, professional ethics and spirituality have been explained and components and 8 stages of operational model of cascading values and professional ethics in different layers of organization have been presented.
Keywords: moral; professional ethics; organizational values; business; human resource development